Evaluation of volume holographic optical elements in dichromated gelatin - Blair, L; Blair, Loudon Thomas (1989)
﻿The use of dichromated gelatin (DCG) for the formation of holographic optical elements is investigated. In particular, a study is made of the possible sources of spurious recording and replay in such diffracting media. The formation of spurious gratings due to boundary mismatch, when recording a transmission grating in air, is investigated. Experimental results are treated using a simple linear theory which is capable of predicting the relative modulation strengths of each of six recorded gratings. The efficiencies of each of these gratings is related to Fresnel's Laws of reflection and therefore the beam ratio. A brief experimental study of the beam ratio is made. It is found that linear theories do not explain replay of gratings recorded at high exposure energies. This is because DCG exhibits a saturating recording characteristic. A theoretical model is developed to verify experimental results of modulation versus exposure energy for the recording of single and double exposure transmission gratings and their subsequent harmonics. This gives good agreement for most cases, however, it does not explain fully the replay of a difference grating formed due to nonlinearities in the double exposure hologram. A coupled wave theory is therefore developed to take account of both multiple grating interactions between the two primary recordings and the recording of a third grating with a spatial frequency equal to the difference of the two fundamental frequencies. The model gives good agreement with experimental results for varying replay angles and wavelengths. DCG is finally used as a tool to investigate the formation of noise gratings in silver halide emulsions. In particular, results are presented for experiments which were performed to study the effect of high angular scatter upon the selectivity of the noise grating and the recording of reflection noise gratings.